Rapid prediction of adverse outcomes for acute normotensive pulmonary embolism: derivation of the Calgary Acute Pulmonary Embolism score. Issue 2 (19th April 2021) - Solverson, Kevin; Humphreys, Christopher; Liang, Zhiying; Prosperi-Porta, Graeme; Andruchow, James E.; Boiteau, Paul; Ferland, Andre; Herget, Eric; Helmersen, Doug; Weatherald, Jason
Background: Acute pulmonary embolism (PE) has a wide spectrum of outcomes, but the best method to risk-stratify normotensive patients for adverse outcomes remains unclear. Methods: A multicentre retrospective cohort study of acute PE patients admitted from emergency departments in Calgary, Canada, between 2012 and 2017 was used to develop a refined acute PE risk score. The composite primary outcome of in-hospital PE-related death or haemodynamic decompensation. The model was internally validated using bootstrapping and the prognostic value of the derived risk score was compared to the Bova score. Results: Of 2067 patients with normotensive acute PE, the primary outcome (haemodynamic decompensation or PE-related death) occurred in 32 (1.5%) patients. In simplified Pulmonary Embolism Severity Index high-risk patients (n=1498, 78%), a multivariable model used to predict the primary outcome retained computed tomography (CT) right–left ventricular diameter ratio ≥1.5, systolic blood pressure 90–100 mmHg, central pulmonary artery clot and heart rate ≥100 beats·min −1 with a C-statistic of 0.89 (95% CI 0.82–0.93). Three risk groups were derived using a weighted score (score, prevalence, primary outcome event rate): group 1 (0–3, 73.8%, 0.34%), group 2 (4–6, 17.6%, 5.8%), group 3 (7–9, 8.7%, 12.8%) with a C-statistic 0.85 (95% CI 0.78–0.91). In comparison the prevalence (primary outcome) by Bova risk stages (n=1179) were stage I 49.8% (0.2%); stage II 31.9% (2.7%); and stage III 18.4% (7.8%) with a C-statistic 0.80 (95% CI 0.74–0.86). Conclusions: A simple four-variable risk score using clinical data immediately available after CT diagnosis of acute PE predicts in-hospital adverse outcomes. External validation of the Calgary Acute Pulmonary Embolism score is required. Derivation of a simple four-variable risk score that uses parameters available at the time of PE diagnosis to risk stratify acute normotensive PE patients, which may help clinicians better decide how to monitor and treat patients https://bit.ly/37PdyrM